KUBOTA Industry Class Study (Case Study at SMK Islam 1 Blitar) - Agustian Yohan Effendi; Syarif Suhartadi; Imam Alfianto (South Sulawesi Education Development (SSED), 2024)
Industrial classes are work experiences for students who are preparing themselves to adapt to the work environment, develop practical skills, and determine appropriate career choices. This research explores the implementation of Kubota industrial classes at SMK Islam 1 Blitar as an approach to preparing students for the world of work. The research method used is qualitative, with a case study and data collected through observation, documentation, and interviews. The results show that the cooperation between the school and industry allows for the integration of theoretical and practical learning, as well as specialized training for students. The preparation and implementation of industrial classes involve an important role for both SMK and business and industry world, with the support of adequate facilities and infrastructure. Supporting factors include the availability of facilities and close cooperation between schools and industries, while inhibiting factors include low student interest and limited resources. Impacts of the industrial classes include improved student skills, school reputation, and the supply of skilled labor for industry. Evaluation is conducted through summative evaluations and certification tests, assessing student progress and ensuring the fulfillment of industry standards. Thus, the Kubota industrial class at SMK Islam 1 Blitar is an effective model for preparing students for challenges in the world of work.